2011
DOI: 10.1016/j.imlet.2011.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Induction of regulatory T cells by green tea polyphenol EGCG

Abstract: Regulatory T cells (Treg) are critical in maintaining immune tolerance and suppressing autoimmunity. The transcription factor Foxp3 serves as a master switch that controls the development and function of Treg. Foxp3 expression is epigenetically regulated by DNA methylation, and DNA methyltransferase (DNMT) inhibitors can induce Foxp3 expression in naive CD4+ T cells. We showed that EGCG, a major green tea polyphenol, could act as a dietary DNMT inhibitor, and induced Foxp3 and IL-10 expression in CD4+ Jurkat T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 35 publications
4
80
0
1
Order By: Relevance
“…26,27) Especially, more recent study explained that condensed tannins induced Foxp3 and IL-10 expression in Jurkat T cells and increased Tr1 frequencies and numbers in vivo. 28) Therefore, RM-3 might reduce oxidative stress and pro-inflammatory signaling pathway in skin allergic inflammation, and activate Treg, leads to down-regulate Th2 cytokines-mediated immune system in this study.…”
Section: Effects On Clinical Skin Severitymentioning
confidence: 67%
“…26,27) Especially, more recent study explained that condensed tannins induced Foxp3 and IL-10 expression in Jurkat T cells and increased Tr1 frequencies and numbers in vivo. 28) Therefore, RM-3 might reduce oxidative stress and pro-inflammatory signaling pathway in skin allergic inflammation, and activate Treg, leads to down-regulate Th2 cytokines-mediated immune system in this study.…”
Section: Effects On Clinical Skin Severitymentioning
confidence: 67%
“…Wong et al [29] reported that EGCG, at physiologically relevant concentrations in vitro, inhibited DNMT and induced the transcription factor Foxp3. In addition, it was shown that in the in vitro culture system, EGCG also reduced the gene expression of all three DNMTs (DNMT 1, DNMT3a and DNMT3b), which correlated with reduced DNA methylation in the Jurkat T cells treated with EGCG [29].…”
Section: Resultsmentioning
confidence: 99%
“…Regulatory T cells (T-reg) are essential in maintaining immune functions by targeting sites of sustained inflammation [28]. Recent in vitro and in vivo studies showed that EGCG (2-50 μM) induced T-reg via the up-regulation of Foxp3, i.e., a transcription factor regulated by DNA methylation [29]. The effect of EGCG on Foxp3 gene expression was similar to that of DNA methyltransferase inhibitors.…”
Section: Inflammationmentioning
confidence: 95%